Study of the Sinergy Effect of Using Accounting Information in the Process of Lending and Risk Management in Banks (UNWE Yearbook, 2017)
This article is a follow-up on the authors' research on the relationship and interdependence between accounting information, accounting analysis, and credit risk management in banks. Analysis of the quality of the loan portfolio, as well as bringing the key trends in the management of credit risk out are processes that need to be modernized, given the dynamics of economic phenomena in the banking sector. The purpose of this study is to present procedures for accounting analysis and credit risk assessment, and recognition of expected credit losses corresponding to the philosophy of IFRS 9 Financial Instruments.